2008
DOI: 10.1097/opx.0b013e31818e8eaa
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Wavefront-Guided Soft Lenses in Three Keratoconus Subjects

Abstract: Purpose-To examine if custom wavefront-guided soft contact lenses provide visual and optical performance equivalent to habitual gas permeable (GP) corrections in three keratoconus subjects.Methods-Custom wavefront-guided soft contact lenses were produced and evaluated at the Visual Optics Institute, College of Optometry, University of Houston for three habitual GP-wearing keratoconus subjects. Photopic high and mesopic low contrast logMAR visual acuity and residual 2nd-10th order optical aberrations experience… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
68
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(74 citation statements)
references
References 23 publications
3
68
1
1
Order By: Relevance
“…O escaneamento de pontos individuais possibilita a capacidade de medidas em olhos com distorções ópticas mais acentuadas, sendo uma vantagem em caso de ceratocone (81) . A aberrometria pode fornecer dados para confecção de lentes de contato gelatinosas personalizadas com correção para as aberrações de alta ordem (82,83) . Tais alternativas poderão ser utilizadas comercialmente em breve, mas ainda não estão disponíveis no mercado brasileiro no tempo da escrita deste artigo.…”
Section: Discussionunclassified
“…O escaneamento de pontos individuais possibilita a capacidade de medidas em olhos com distorções ópticas mais acentuadas, sendo uma vantagem em caso de ceratocone (81) . A aberrometria pode fornecer dados para confecção de lentes de contato gelatinosas personalizadas com correção para as aberrações de alta ordem (82,83) . Tais alternativas poderão ser utilizadas comercialmente em breve, mas ainda não estão disponíveis no mercado brasileiro no tempo da escrita deste artigo.…”
Section: Discussionunclassified
“…23 Third, the decentration of the resting position of the lens is associated with a reduction of the correction. Although custom-made SCLs were designed to correct all HOA components in the previous studies as reported by Marsack et al 20 or all the third-order coma aberration, as reported by Jinabhai et al, 21 they could not always achieve 100% correction. Both these studies suggested that the undercorrection could be due to the decentration of the lenses.…”
Section: Discussionmentioning
confidence: 99%
“…Marsack et al 20 described an attempt to correct irregular astigmatism in patients with keratoconus using custom-made SCLs created to fully correct all ocular HOAs based on Zernike polynomials and reported that the visual performance was significantly improved in the patients, although the correction was not 100%. Jinabhai et al 21 and Katsoulos et al 8 used custom SCLs designed to achieve 50% to 100% correction of third-order coma aberration, and their results showed that the visual performance of patients with keratoconus improved without correcting all the Zernike terms.…”
Section: Discussionmentioning
confidence: 99%
“…Customized refractive surgical procedures are being developed in which the static wavefront of every person's eyes are measured precisely and mapped to the corneal. Many researchers are also working on custom spectacles, contact lenses, and intraocular lenses that have a shape tailored to one's eye [220][221][222].…”
Section: Adaptive Opticsmentioning
confidence: 99%